Clinicopathological features of five unusual cases of intraosseous myoepithelial carcinomas, mimicking conventional primary bone tumours, including EWSR1 rearrangement in one case. Issue 4 (14th January 2016) - Rekhi, Bharat; Joshi, Sujit; Panchwagh, Yogesh; Gulia, Ashish; Borges, Anita; Bajpai, Jyoti; Jambehekar, Nirmala A.; Pant, Vinita; Mandholkar, Mahesh; Byregowda, Suman; Puri, Ajay
Abstract : Primary intraosseous myoepithelial tumours, including carcinomas are rare tumours. The concept of histopathological spectrum of these tumours is evolving. We describe clinicopathological and immunohistochemical features of five myoepithelial carcinomas, including molecular cytogenetic results in one case. There were five male patients within age‐range of 8–40 years (median = 26). Four tumours occurred in the long bones, including two tumours, each, in the femur and fibula, respectively, while a single tumour occurred in the proximal phalanges. Tumour size (n = 3 cases) varied from 5.6 to 8.6 cm. On radiological imaging, most tumours appeared as expansile, lytic and destructive lesions. Two tumours appeared as sclerotic lesions. Two cases were referred with diagnoses of chondrosarcomas and a single case was referred with two different diagnoses, including an adamantinoma and an osteosarcoma. Histopathological examination in all these cases showed multinodular tumours comprising mostly polygonal cells, exhibiting moderate nuclear atypia and interspersed mitotic figures within a stroma containing variable amount of myxoid, chondroid, hyalinised and osteoid‐like material. Three tumours revealed prominent squamous differentiation. By immunohistochemistry, tumour cells were positive for EMA (5/5), pan CK (AE1/AE3) (3/3), CK5/6 (4/4), CK MNF116 (1/1), S100 protein (5/5) and GFAP (3/5). The first tumour revealed EWSR1 rearrangement. The first patient, 10 months after tumour resection and a simultaneous lung metastatectomy, is free‐of‐disease (FOD). The second patient, 11 months after tumour resection is FOD. The third and fourth patients underwent wide resections and are on follow‐up. The fifth patient underwent resections, including a lung metastatectomy. Primary intraosseous myoepithelial carcinomas are rare and mimic conventional primary bone tumours. Some primary intraosseous myoepithelial carcinomas display EWSR1 rearrangement. Squamous differentiation may be considered as an addition to their evolving histopathological spectrum. Immunohistochemical stains constitute as a necessary tool for arriving at the correct diagnosis in such cases, which has treatment implications. Surgical resection remains the treatment mainstay.